Hábitos de vida dos trilobitas das formações Maecuru e Ererê (Devoniano), Bacia do Amazonas - Silva, Cleber Fernandes da (2004)
Fourteen species of trilobites were identified from the Maecuru Formation and one from Ererê Formation (Devonian, Amazon Basin), sampled at Pará State, Brazil. Seven species from the Maecuru Formation and the species from the Ererê Formation were submitted to the morph functional analysis, because the presence of cephalous and/or hypostome well–preserved. These species were grouped into three morphotypes: morphotype I – Homalonotus derbyi – presents glabella, with shallow glabellar furrows, and glabellar frontal lobe weakly inflated; morphotype II – Phacopina brasiliensis, “Dalmanites” (gen. nov. aff. Fenestraspis) maecurua, “D.” (gen. nov. aff. Vogesina) galeus, “D.” (gen. nov. aff. Malvinella) tumilobus and Eldredgeia paituna (a complete specimen, described here, at the first time) – presents a fixed conterminant hypostome, medium size eyes, glabella moderately inflated, glabellar frontal lobe differentiated from the others and glabellar furrows deeper than morphotype I; morphotype III – “Malvinela” australis and “Palpebrops” goeldii – presents glabella and glabellar frontal lobe strongly inflated, glabellar furrows shallow to moderately shallow, and medium size eye, approximately in the same height of the glabella. All morphotypes shows predator/scavenger feeding habits. The morphotypes I and II present burrow adaptations, more developed in the morphotype I, and therefore suggests a semiinfaunistic mode of life. These adaptations were used probably to feeding and protection against predators and environmental disturbances. The morphotyape III is characterized by predominantly epifaunistic habits and shows greater stomach cavity, and were probably more voracious predators than the others morphotypes. The Maecuru Formation presents two different fossiliferous concentrations: the bioclasts of the point OAD 3, which were probably parautochthonous and deposited by storm waves; and the blioclasts from the Maecuru River, OAD 4 and OAD 4A points, which could indicate different depositional events, time averaging and allochthonous and/or parautochthonous assemblages. The Ererê Formation presents allochthonous and/or parautochthonous concentrations at the sandstone beds and autochthonous to parautochthonous at the shale beds.